simplify 11 - 2m-(n + 5+-m - 3n + 8)

11 - 2m-(n + 5+-m - 3n + 8) =(-2m + m)+(- n + 3n)+(11 +(-5)+(-8)) = - m + 2n - 2

Question

Asked 2/17/2016 8:43:33 AM

Updated 2/17/2016 9:00:28 AM

1 Answer/Comment

Rating

3

11 - 2m-(n + 5+-m - 3n + 8)

=(-2m + m)+(- n + 3n)+(11 +(-5)+(-8))

= - m + 2n - 2

=(-2m + m)+(- n + 3n)+(11 +(-5)+(-8))

= - m + 2n - 2

Added 2/17/2016 9:00:28 AM

This answer has been confirmed as correct and helpful.

Simplify (x - y + 1) - (x + y - 1).
**Weegy:** (x - y + 1) - (x + y - 1) = x - y + 1 - x - y + 1 = (x - x) + (-y - y) + (1 + 1) = -2y + 2 **User:** Simplify (3x + 5) + (2x - 9) - (4x + 3) **Weegy:** (3x + 5) + (2x - 9) - (4x + 3) = (5x - 4) - (4x + 3) = (5x - 4) + (-4x - 3) = x - 7 **User:** Simplify -(-2a + 13) + (-9a - 2) - (-7a - 3) **Weegy:** -(-2a + 13) + (-9a - 2) - (-7a - 3) = 2a - 13 - 9a - 2 + 7a + 3 = -12 **User:** Simplify 3j - {2k - [5h - (3j + k)]}. **Weegy:** 3j - {2k - [5h - (3j + k)]} = 5h - 3k **User:** Simplify {n - 1 - [n - 1 - (n - 1)]}. **User:** Simplify a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]}.
**Weegy:** a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]} = a - [5b - (a - 3b + 2c + c - a + 2b + c)] = a - [5b - (-b + 4c)] = a - (5b + b - 4c) = a - (6b - 4c) = a - 6b + 4c **User:** Simplify 2m - [n - (m - 2n)]. **Weegy:** 2m - [n - (m - 2n) is equal to 3m -3n. SOLUTION: 2m - [n - (m - 2n)]. 2m - [n - m + 2n]. 2m - n + m - 2n. 2m + m - n - 2n. 3m - 3n. (More)

Question

Updated 2/17/2016 11:49:56 PM

1 Answer/Comment

29,506,138

questions answered

There are no comments.